An experimental study of the wave effect in fuel equipment using hydrogen additives to diesel fuel - Shalapko, Denis (Technology audit and production reserves, 2018)
The object of research is the hydrodynamic wave effects in the fuel equipment of high pressure diesel engines. One of the most problematic phenomena when using hydrogen additives to diesel fuel is the change in the maximum fuel injection pressure, which leads to deterioration of fuel separation parameters. For research on the nature of hydraulic oscillations in the fuel equipment, an experimental booth has been created that allows the study of the wave effect with the use of small additives of hydrogen to the main fuel. In the development of an experimental stand, modern precision measuring instruments were used. According to the results of experimental studies, it is established that in the high pressure fuel line a characteristic «wave effect» of oscillations appears. This effect is caused by the landing of the pressure valve on the saddle in the fuel pump of high pressure, as well as the landing of the needle nozzle. The nature of the oscillation depends on factors such as the length of the pipeline between the pump and the nozzle, the maximum injection pressure of diesel fuel, the speed of propagation of the pressure wave. This speed, in turn, depends on the frequency of rotation of the crankshaft of the engine. The frequency of rotation of the fuel pump shaft is changed with the help of an inverted regulator and frequency meter of the drive motor. As a result, the fuel injection characteristics are obtained, which reflect the nature of the change in the pressure wave, depending on the presence of hydrogen additive. It is determined that the hydrogen additive in the amount of 0.1 % of the cycle fuel supply (by mass) leads to the suppression of wave oscillations and the shortening of the oscillation region by 12...20. The characteristics of absorption of hydrogen by diesel fuel are obtained. The amount of hydrogen additive depends on the pump rotation frequency, the injection pressure and the supply pressure of the additive. This kind of hydrogen consumption is explained by the time frame of the restriction of the absorption process, the difference in the minimum value of the «pressure wave» of the excess pressure of the additive. The resulting data can be used to confirm the mathematical model of hydrogen absorption when used as an additive to the fuel line.